Ferric pyrophosphate fortified extruded rice increased iron status in rats - Akinbo, David Bolaji (Kansas State University, 2022)
Background: Iron deficiency is the most common micronutrient deficiency worldwide and one of the five prominent causes of years lived with disability in humans, particularly affecting women and children. Ferric pyrophosphate (FePP) and ferric phosphate (FePO₄) are commonly used in fortifying rice due to their minimal impacts on its sensory properties, but have both presented with poor iron bioavailability. Particle-size reduction of FePP and addition of ligands such as citric acid (CA) and trisodium citrate (TSC) to extruded FePP-fortified rice have been associated with improved iron bioavailability in iron-fortified rice. Objective: To compare the iron outcomes of extruded rice flour formulated with four different iron fortificants in rats. Methods: Using the prophylactic-preventative method, 50 male weanling Sprague-Dawley rats aged 20-23 days were randomly distributed into 5 groups and fed ad libitum for a 28-day period. The control group consumed powdered AIN-93G growth diet, while the other four experimental diets were AIN-93G based extruded rice flour diets fortified with micronized FePP (μFePP), a higher FePP concentration, FePO₄ with TSC and CA or FePP with TSC and CA at a molar ratio of 1:0.3:5.5 for iron to TSC/CA. Hematological parameters and hepatic iron concentration were assessed for the iron status. The dual energy x-ray absorptiometry (DEXA) PIXImus scan was used to assess the bone mineral density (BMD) and body composition of the rats. Results: The consumption of FePP, μFePP, FePP+TSC+CA fortified rice flour significantly increased (p<0.05) hepatic iron concentration compared to the FePO₄+ TSC+CA fortified rice flour and AIN-93G groups. However, there were no significant differences between the hepatic iron concentrations of the FePP groups or the hematological and anthropometric assessments between all groups (p>0.05). Conclusion: Increased concentration of FePP in extruded fortified rice can improve iron status, and suggests that neither micronizing FePP nor extruding it with TSC and CA improved iron status compared to FePP. The extrusion of FePO₄ with TSC and CA did not improve iron status.
Keywords: Iron; Fortification; Rice; Extrusion; Ferric pyrophosphate; Ferric phosphate